PENCEGAHAN DAN PENANGANAN BENCANA DAERAH DI KABUPATEN NGADA - Lobo, Ferdinandus; Pedo, Yustinus; Fernanda Maia, Ledythria; Louisa Henukh Ledoh, Putri Marry; Snak, Stefanus (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Disaster prevention and management in the Ngada Regency area requires a comprehensive and coordinated approach to reduce the risks and impacts caused. Ngada Regency, located in East Nusa Tenggara Province, has its vulnerability to natural disasters such as floods, landslides, and forest fires. Prevention efforts involve increasing public awareness through disaster mitigation education and training, as well as building disaster-resilient infrastructure. In addition, coordination between local governments, disaster management agencies, and communities is essential to create an effective early warning system and clear evacuation procedures. Disaster management in Ngada Regency requires preparedness, adequate resource organization, and rapid response in emergency situations. This study aims to identify effective disaster prevention and management strategies and assess the role of the community and the government in disaster management in this region. The results of the study are expected to provide recommendations for policy makers to strengthen regional capacity and resilience to natural disasters.